Food Demand and Consumption Patterns in the New EU Member States: The Case of Slovakia - Andrej Cupák; Ján Pokrivčák; Marian Rizov (Ekonomický časopis, 2015)
We estimate a food demand system for Slovakia using a recent Household Budget Survey data collected by the Slovak statistical office covering the period 2004 – 2010. The Quadratic Almost Ideal Demand System (QUAIDS) augmented with demographic, regional and expenditure controls is employed based on preliminary non-parametric Engel curve analysis. Results indicate that demand for dairy products and fruits and vegetables is expenditure and own-price elastic indicating that such goods are perceived as luxuries. On the other hand, commodity bundles such as cereals, meat and fish and other food are found to be normal goods with positive budget elasticity smaller than one and price inelastic demand. Rural and low-income households appear more expenditure and, especially, price sensitive compared with the urban and high-income ones. Overall the food consumption patterns changed and food security situation improved in Slovakia between 2004 and 2010.
Keywords: D12; I12; O52; Q18; 330; elasticity; food demand; QUAIDS; Slovakia